The position of the Arabs from the Soviet occupation of Afghanistan 1979 - 1989 - فاضل مجيد الربيعي, مي (Al-Adab Journal, 2018)
This study sheds light on the role of Arab volunteers in support of the Afghan resistance against the Soviet occupation. Starting with the Afghan resistance movement, which has raised as a reaction to the Soviet invasion of their territory and the most important jihadist organizations that led the resistance war and then the study addressed the responses of the international, Islamic and Arab occupation against this occupation and it focused on the role of Saudi Arabia, Egypt and the Gulf states, which effectively contributed to the financial and moral support to the Afghan resistance movement then it mentioned the beginning of the Arab presence in Afghanistan and the volunteers relief and humanitarian role in Peshawar and then the combat role and participation in battles against Soviet forces and finally the fate of these volunteers after the Soviet withdrawal from Afghanistan.